Stepwise Progression of Right-to-Left Atrial Shunting through a Combination of Patent Foramen Ovale and Tricuspid Regurgitation - Kransdorf, Evan P. (Tex Heart Inst J, 2016)
Patent foramen ovale is a common clinical finding that generally becomes a concern in the presence of transient ischemic attack or stroke. Rarely, patent foramen ovale is associated with hypoxemia in the presence of substantial right-to-left atrial shunting. We present the case of an 86-year-old woman with a pacemaker, who was initially asymptomatic notwithstanding a patent foramen ovale. Over 1.5 years, her symptoms progressed in a stepwise fashion, in the setting of progressive pacemaker-associated tricuspid regurgitation. Ultimately, the patient's symptoms and her hypoxemia resolved after percutaneous closure of her patent foramen ovale with use of a 25-mm “Cribriform” occluder device. This case highlights the fact that clinically significant right-to-left shunting requires an anatomic lesion, such as patent foramen ovale, together with elevated right atrial pressure, which in this case was contributed by severe tricuspid regurgitation.